Improved Uniform Current Injection into Core‐Shell‐Type GaInN Nanowire Light‐Emitting Diodes by Optimizing Growth Condition and Indium‐Tin‐Oxide Deposition. Issue 7 (27th November 2019) - Sone, Naoki; Suzuki, Atsushi; Murakami, Hideki; Goto, Nanami; Terazawa, Mizuki; Lu, Weifang; Han, Dong-Pyo; Iida, Kazuyoshi; Ohya, Masaki; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; et al.
Abstract : The aim of this research is to realize high‐efficiency light‐emitting diodes (LEDs) with a 3D core‐shell GaN nanowire. This article describes the growth of 3D core‐shell GaN nanowires, the formation of indium tin oxide (ITO) around the p‐GaN outer shell of the nanowires, and the characteristics of the fabricated nanowire‐LED (NW‐LED). The structural properties of the n‐GaN core, GaInN/GaN multiquantum shell (MQS), p‐GaN outer shell, and ITO electrode are investigated by scanning electron microscopy and scanning transmission electron microscopy. In addition, the optical and electrical characteristics of the NW‐LEDs are evaluated. The findings show that the grown n‐GaN cores have a uniform height and diameter, the MQS is defect‐free with a uniform film thickness, and p‐GaN outer shells with a uniform thickness are grown on both the m ‐ and c ‐planes. Consequently, a NW‐LED that emits light from the entire chip area is successfully realized by depositing an ITO electrode that covers the p‐GaN outer shells with a uniform film thickness. Abstract : Herein, the formation of indium tin oxide (ITO) around the p‐GaN outer shell of nanowire light‐emitting diode (NW‐LED) and the characteristics of the NW‐LED are described. The NW‐LED emits light from the entire growth area. In particular, the formation of uniform‐thickness ITO electrodes is considered to have contributed greatly to the result.